A Survey of Indicators of Fat Content and Body Mass Index on the Physical Condition of Martial Arts Athletes in Kota Batu Ahead of the East Java Porprov VII - Moch Yunus; Eldiene Zaura I'tamada; Zihan Novita sari (UNIB Press, 2022)
Physical conditions as a reference for athletes' abilities can be used as a supporting process for evaluation materials for coaches and athletes in assessing the abilities of their athletes after the training process is carried out. Some things that support the physical condition of athletes include anthropometry, fat content, body mass index (BMI), nutrition, psychology, environment, and the training process in each sport. In this case, BMI and fat content are part of this study to identify the relationship between physical condition and BMI and body fat levels of Kota Batu martial arts athletes with a total of 45 athletes. T a tool to measure BMI and body fat levels in this study using the Body Composition Analyzer, Tanita DC-360Phe method used in this study is a survey with descriptive data presentation that correlates indicators of fat content, and body mass index with the physical condition of martial athletes which include: (1) arm muscle strength, (2) abdominal muscle strength, (3) leg muscle strength, (4) back muscle strength, (5) balance, (6) leg muscle power, (7) arm muscle power, (8) agility and (9) cardiovascular endurance. The physical fitness level of Kota Batu martial arts athletes has a fairly good percentage with an average score of 76% for male athletes and 77% for female athletes. Athletes have a fairly ideal body condition because the fat mass of all athletes is at normal levels and 33 athletes are at the ideal BMI.